Comparison of Life-Stage-Dependent Internal Dosimetry for Bisphenol A, Ethinyl Estradiol, a Reference Estrogen, and Endogenous Estradiol to Test an Estrogenic Mode of Action in Sprague Dawley Rats - Churchwell, Mona I. (Oxford University Press, 2014)
Bisphenol A (BPA) was administered by gavage (2.5–300,000 μg/kg body weight (bw)/day) to pregnant Sprague Dawley dams, newborn pups, and continuing into adulthood. Aglycone (i.e., unconjugated and active) and conjugated (i.e., inactive) BPA were evaluated by liquid chromatography electrospray tandem mass spectrometry (LC-ES/MS/MS) in serum to better interpret toxicological endpoints measured in the study. Ethinyl estradiol (EE2, 0.5 and 5 μg/kg bw/day) and the endogenous hormones, 17β-estradiol (E2) and testosterone, were similarly evaluated. Mean BPA aglycone levels in vehicle and naïve control rat serum (0.02–0.5 ng/ml) indicated sample processing artifact, consistent with literature reports of a propensity for postexposure blood contamination by BPA. Direct measurements of BPA-glucuronide in vehicle and naïve control serum (2–10nM) indicated unintentional exposure and metabolism at levels similar to those produced by 2.5 μg/kg bw/day BPA (7–10nM), despite careful attention to potential BPA inputs (diet, drinking water, vehicle, cages, bedding, and dust) and rigorous dosing solution certification and delivery. The source of this exposure could not be identified, but interpretation of the toxicological effects, observed only at the highest BPA doses, was not compromised. Internal exposures to BPA and EE2 aglycones were highest in young rats. When maximal serum concentrations from the two highest BPA doses and both EE2 doses were compared with concurrent levels of endogenous E2, the ERα binding equivalents were similar to or above those of endogenous E2 in male and female rats of all ages tested. Such evaluations of estrogenic internal dosimetry and comprehensive evaluation of contamination impact should aid in extrapolating risks from human BPA exposures.